The impact and mechanism of digital economy on agricultural development resilience: evidence from China - Xuandeng Xue; Jialin Gao; Shijie Xu (Frontiers in Sustainable Food Systems)
IntroductionWith the booming development of the digital economy, the integrated development of digital technology and agriculture continues to expand and deepen. Clarifying the impact and mechanisms of digital economy on agricultural development resilience is of great significance for sustainable agricultural development.MethodsBased on the provincial panel data of 13 major grain-producing regions in China from 2010 to 2020, the evaluation system of digital economy and agricultural development resilience were constructed, and the entropy-TOPSIS method was used to measure them. Using the panel Tobit model, the mediation effect model and the threshold regression model, the impact effects and the mechanism of digital economy on agricultural development resilience were explored.ResultsThe results show that digital economy has a positive effect on agricultural development resilience, and this conclusion remains valid after a series of robustness tests. Mechanism analysis reveals that mitigating the misallocation of agricultural resources is a crucial pathway through which the digital economy enhances agricultural development resilience. Furthermore, the threshold effect analysis suggests that the digital economy’s role in promoting agricultural development resilience exhibits a non-linear characteristic, with increasing marginal effects. Additionally, the heterogeneity analysis indicates that the impact of the digital economy on agricultural development resilience varies regionally, with a notably stronger positive effect on the eastern region compared to the central and northern regions.DiscussionThis study provides empirical evidence that the digital economy enhances the resilience of agricultural development and provides relevant policy recommendations for the government, which is important for promoting sustainable agricultural development.